Analisis Pelaksanaan Ujian Semester Berbasis WEB Mata Pelajaran Sejarah di Madrasah Aliyah Negeri 1 Pekanbaru - Rahmad Dandi; Bedriati Ibrahim; Asril Asril (Keraton: Journal of History Education and Culture, 2022)
Today, the people of the World including Indonesia have entered the era of industrial revolution 4.0 which is characterized by increasing internet connectivity, as well as the rapid development of information and communication technology (ICT). Efforts to improve the quality of human resources (HR) through education channels are the main key in following the development of the industrial revolution 4.0, one of which can be achieved by optimizing the use and application of digitalization technology in education. Madrasah Aliyah Negeri 1 Pekanbaru applies web-based semester exams in the process of assessment and evaluation of students' learning. This study uses qualitative approach. The results of the study implementation of web-based semester exams history subjects in MAN 1 Pekanbaru there are four stages conducted, namely the petrencanaan stage, the organizing stage, the implementation stage and the reporting stage.While the inhibitory factors of the implementation of web-based semester exams are power outages and network loss, devices that often experience problems, exam problems that appear incomplete. The impact of the implementation of web-based semester exams on the effectiveness of historical learning assessment at MAN 1 Pekanbaru is economical, time effectiveness, assessment objectives and easy and flexible.